2021
DOI: 10.1016/j.celrep.2021.109762
|View full text |Cite
|
Sign up to set email alerts
|

ULK1 phosphorylation of striatin activates protein phosphatase 2A and autophagy

Abstract: Highlights d ULK1 regulates autophagosome expansion, maturation, and lysosomal fusion d ULK1 regulates an elaborate protein phosphatase network d ULK1 and striatin are linked by a regulatory feedback mechanism d Phosphorylation of striatin by ULK1 promotes functional autophagy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 81 publications
0
21
0
Order By: Relevance
“…To further discriminate direct from indirect effects, we performed whole proteome on bead in vitro kinase assays (OBIKA) comparing the immobilized proteome of snf1 as cells growing exponentially in 5% Glucose in the presence of ATP analog, incubated with purified wild-type Snf1 to that incubated with a kinase-inactive Snf1 T210A mutant (Fig. 3A; n=5 biological replicates) (Hu et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further discriminate direct from indirect effects, we performed whole proteome on bead in vitro kinase assays (OBIKA) comparing the immobilized proteome of snf1 as cells growing exponentially in 5% Glucose in the presence of ATP analog, incubated with purified wild-type Snf1 to that incubated with a kinase-inactive Snf1 T210A mutant (Fig. 3A; n=5 biological replicates) (Hu et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…To dissect the mechanisms by which Snf1 impinges on TORC1 signaling, we decided to perform a set of stable isotope-labeling by amino acids in cell culture (SILAC)-based quantitative phosphoproteomic experiments, similarly as recently described (Hu et al, 2021). For in vivo analyses, snf1 as cells were grown in three different SILAC media supporting the comparison of three experimental conditions (Fig.…”
Section: Global Phosphoproteomics Identifies Potential Snf1 Targets W...mentioning
confidence: 99%
“… Function The substrate protein Modified site Positive regulation/ negative regulation Modification enzyme Ref. Phosphorylation ULK1 Ser317, Ser777, Ser555, Thr574, Ser637, Ser467 Activate AMPK 12 , 103 , 106 Phosphorylation ULK1 Ser757/758, Ser638, Ser467 Inhibit mTOR 103 , 104 Phosphorylation mTOR Ser2481 Inhibit ULK1 107 Phosphorylation S6k1 Thr389 Inhibit ULK1 107 Phosphorylation Raptor Ser863, Ser855, Ser859, Ser792 Inhibit ULK1 107 Phosphorylation ULK1 Ser317, Ser555 Activate MAPK15 108 , 109 Phosphorylation ULK1 Ser405, Ser415 Activate GSK3 β 110 Phosphorylation ULK1 Ser423, Ser317/555/777 Inhibit PKC α 111 , 112 Phosphorylation ULK1 Ser555, Ser757 Inhibit WNK1 113 , 114 Phosphorylation ULK1 / Activate PP2A 115 Deubiquitination …”
Section: The Molecular Basis Underlying the Regulation Mechanism Of Ulk1mentioning
confidence: 99%
“…Through phosphorylation proteomic analysis, combined with relevant experimental data, studies found that ULK1 can directly phosphorylate and promote the regulation of PP2A subunit striatum. Activated PP2A enhances autophagy through positive feedback regulation, promotes protein transport, and degrades proteins 115 . Beside the above phosphorylation regulation, there are many other proteins that regulate the phosphorylation of ULK1 ( Table 2 ), and contribute to the functions of ULK1.…”
Section: The Molecular Basis Underlying the Regulation Mechanism Of Ulk1mentioning
confidence: 99%
“…In some cases, Wt cultures were treated for 24h with IBA, CLX (each 10 μM) or Fo5176 elicitor (250 ug/ml) for 24h or exposed to Fo699 for 24h by addition of 10 7 conidia/ml. Total microsomes were prepared and trypsin digest was processed by using the FASP protocol overnight (Wiśniewski et al, 2009); phoshopeptides were enriched by TiO2 affinity beads (Hu et al, 2021). The tip flow-through was desalted by STAGE tips for non-phosphopeptide analysis.…”
Section: Protein Phosphorylation Analyses By Lc-ms/msmentioning
confidence: 99%